Shakespeare and the Victorians - Sillars, Stuart (UK Oxford University Press, 2013)
OXFORD SHAKESPEARE TOPICS General Editors: Peter Holland and Stanley Wells Oxford Shakespeare Topics provide students and teachers with short books on important aspects of Shakespeare criticism and scholarship. Each book is written by an authority in its field, and combines accessible style with original discussion of its subject. The book shows how the reception and remodelling of the works and the man directed the Victorian construction of identity, personal, national and aesthetic, as well as laying foundations that later Shakespeareans could continue, extend or reject. Shakespeare was one o.
Include Index and Illustration
Keywords: Shakespeare, William, 1564-1616 -- Influence (Literary, artistic, etc.) -- Great Britain